Marcus Simaika : father of Coptic archaeology - Simaika, Samir; Henein, Nevine; Reid, Donald M. (Donald Malcolm), 1940- (:Cairo The American University in Cairo Press, 2017)
Draws upon Simaika's unpublished memoirs as well as on other documents and photographs from the Simaika family archive to deepen our understanding of several important themes of modern Egyptian history: the development of Coptic archaeology and heritage studies, Egyptian-British interactions during the colonial and semi-colonial eras, shifting balances in the interaction of clergymen and the lay Coptic community, and the ever-sensitive evolution of relations between Copts and their Muslim compatriots--
The Simaika family tree -- Chronology -- Acknowledgments -- Preface -- List of illustrations. Introduction / Donald M. Reid. Part 1 The early years : Cairo -- A love of learning -- A prominent family. Part 2 Service to government and nation : The state railways -- Education and legislation : The Superior Council of Education -- The Legislative COuncil and the Legislative Assembly -- Simaika and the British administrator : Lord Cromer (1883-1907) -- Sir Eldon Gorst (1907-11) -- Field Marshal Lord Kitchener (1911-14) -- Sir Henry McMahon (1914-17) -- Sir Reginald Wingate (1917-19) -- Lord Allenby (1919-25) -- Lord Lloyd (1925-29). Part 3 Service to the Coptic church and community : An ancient church : Monks and missionaries -- The Copts after the Arab conquests -- The rise of Coptic notables -- The patriarchs : Cyril IV (1854-61) -- Cyril V (1874-1927) -- Yohannes XIX (1928-42) -- The awakening of the Coptic church -- Al-Majlis al-Milli -- The Coptic and Ethiopian dispute over Deir al-Sultan in Jerusalem -- Travels in Sudan. Part 4 The Coptic Museum and heritage preservation : A crumbling heritage -- The Committee for the Preservation of Arab Art -- A new museum : The Mu'allaqa Church -- The Coptic Museum -- A state institution -- Searching for iniquities, saving libraries -- Recognition. Appendix: some Coptic social customs -- Selected bibliography -- Notes -- Index.
Includes bibliographical references (pages 179-181) and index.
Keywords: Simaykah, Murqus, -- 1864-1944.